The effect of the growth rate on microsegregation: Experimental investigation in hypoeutectic Al–Fe and Al–Cu alloys directionally solidified - Meza, Elisangela S.; Bertelli, Felipe; Goulart, Pedro R.; Cheung, Noé; Garcia, Amauri (Journal of alloys and compounds, 2013)
► Microsegregation is fundamental for both as-cast properties/post-casting processes. ► Thermal parameters during transient solidification affect microsegregation. ► The effect of growth rate V on microsegregation profiles is experimentally examined. ► An experimental law incorporating V in microsegregation calculations is proposed. Hypoeutectic Al–Cu and Al–Fe alloys were directionally solidified under unsteady-state heat flow conditions in a water-cooled solidification setup. The experimental cooling curves allowed solidification thermal parameters: tip cooling rate (T˙) and tip growth rate (VL) to be experimentally determined and correlated with the scale of the dendritic (Al–Cu alloys) and cellular (Al–Fe alloys) patterns. Experimental microsegregation profiles from the central part of the dendrite/cell cores to the limit of the interdendritic/intercellular regions were determined for different growth rates. The effect of the growth rate was incorporated into an effective partition coefficient that has been determined for the range of growth rates experimentally examined and both Scheil and Clyne–Kurz models were used in the prediction of microsegregation profiles. It was found that both models have significant deviations from the experimental data. Since the calculated results using the theoretical models yielded appreciable discrepancies from the experimental data, an experimental equation is proposed, showing a good agreement with the experimental data for the entire range of solid fractions and experimental tip growth rates, for any alloy experimentally examined.